Characteristic of Insulation Panel Using Waste Spent Coffee Grounds (SCG) and Cardboard (CB) - NIK ZAIYUMI, NIK NUR SYAHERAH; Syed Zin, Syed Mohd Fareed; Wan Jusoh, Wan Amizah (Progress in Engineering Application and Technology, 2025)
Waste materials have increasingly expanded and have been used as an alternative in the construction industry to implement sustainability elements. The waste accumulation was increasing day by day, including global warming and environmental development that inclined to noise pollution. This experimental study investigates the characteristic waste of Spent Coffee Grounds (SCG) and Cardboard (CB) as an acoustic and thermal insulation application. The investigated composite SCG-CB performance with four proportions with SCG: CB are 30:70, 50:50, 60:40 and 70:30 was prepared using tapioca starch as a natural binder. The composite was mixed by wet mixing. The sample was prepared by manually cold pressing and sun drying. The samples have been tested and concluded with a remarkable performance on each test: a 1.19 α of sound absorption coefficient, 27.32 dB of sound reduction index, and 0.072 W/m.K of thermal conductivity. SCG-CB panels have been compared with product markets such as polyester cotton, which has been tested in the same way as SCG-CB panels. This study shows the applicability of SCG and CB panel insulation as sustainable solutions to conventional insulation materials for acoustic and thermal insulation. Additionally, it transforms the current acoustic and thermal panels into practical, affordable materials through thermal insulation, and at the same time, it promotes sustainable products to the market and community. Moreover, Spent Coffee Grounds and Cardboard have the potential to be alternative materials in panel insulation applications.